Peralihan Regulasi Dari Undang-Undang Nomor 8 Tahun 1971 Ke Undang-Undang Nomor 22 Tahun 2001 Tentang Minyak Dan Gas Bumi - Iskatrinah Iskatrinah; Doni Adi Supriyo (Wijayakusuma Law Review, 2022)
Abstract The enactment of Law Number 22 of 2001 concerning Oil and Gas, is an important milestone in regulating oil and gas mining business in Indonesia. One of the interesting provisions is regarding the production sharing contract. However, in this study, the formulation of the problem that will be reviewed is the history of the birth of Law Number 22 of 2001 concerning Oil and Gas. The method used in this discussion is the normative juridical method through literature studies such as literature books and Law Number 8 of 1971; Law Number 22 of 2001 concerning Oil, Gas and Natural Gas by doing a comparison or comparison of the two laws and regulations. The specifications used in this discussion are Analytical Descriptive, which describes the facts regarding provisions regarding oil and gas and natural gas. In order to fulfill the wishes of foreign investors, the economic reform agenda contained in the letter of intense, includes the energy sector reform program. The energy sector reform is stated in the agreement item letter F (The energy Sector) in the Memorandum of Economic and Financial Policies (Letter of Intense), January 20, 2000. Keywords: Oil and Gas, Mining, Economy Abstrak Lahirnya Undang-undang Nomor 22 tahun 2001 tentang Minyak dan Gas Bumi, merupakan tonggak penting dalam pengaturan pengusahaan pertambangan migas di Indonesia. Salah satu ketentuan menarik adalah tentang kontrak bagi hasil (Production Sharing Contract). Akan tetapi dalam penelitian ini rumusan masalah yang akan diulas adalah mengenai sejarah kelahiran Undang-Undang Nomor 22 tahun 2001 tentang Minyak dan gas Bumi. Metode yang digunakan dalam pembahasan ini adalah metode Yuridis Normatif dengan melalui studi kepustakaan seperti buku-buku literatur dan Undang-Undang No. 8 tahun 1971; Undang-Undang No. 22 tahun 2001 tentang Minyak Gas dan Bumi dengan melakukan komparasi atau perbandingan atas kedua peraturan perundang-undangan tersebut. Spesifikasi dalam pembahasan ini digunakan Deskriptif Analistis, yang menggambarkan fakta-fakta tentang ketentuan mengenai minyak gas dan bumi. Dalam rangka memnuhi keinginan investor asing, agenda reformasi ekonomi yang tertuang dalam letter of intens, diantaranya adalah program reformasi sector energy. Reformasi sector energy tercantum dalam butir kesepakatan huruf F (The energy Sector) dalam Memorandum of Economic and Financial Policies (Letter of Intens), 20 Januari 2000. Kata Kunci: Migas, Pertambangan, Ekonomi